Gaming goes to Hollywood. (Economist, 2004)
The author reports on the trend towards turning Hollywood movies into video games. The latest James Bond adventure is at number one, "Finding Nemo" at number 12, and "The Lord of the Rings" at number 18. A chart of DVD sales or box-office receipts? No, this is last week's British video-games chart, a vivid illustration of how the once-separate worlds of movies and games have become increasingly intertwined. Animators, artists and model-makers move freely between the two worlds; the same companies produce trailers both for games and for films. People in the booming games business are fond of pointing out that worldwide games sales, at around $20 billion a year, now exceed movie box-office revenues. The convergence between films and games makes sense for many reasons. Both special-effects-laden blockbusters and shoot-'em-ups rely on computer power, and as games consoles become more capable their output becomes ever more cinematic. But as movie tie-ins and sequels proliferate, there is concern that creativity is suffering. It is also getting harder for independent developers to secure publishing deals, particularly as the big publishers take more development in-house. Despite the convergence between games and films, the games industry is still different in a number of important respects. For instance, game-making is iterative: it is possible to market-test a game and then modify it, and to do so repeatedly during the game's development cycle--something that is not really possible with a film. That makes the games business far more predictable, and accounts for its far higher returns.